Global Debates in the Digital Humanities - Fiormonte, Domenico (Debates in the digital humanities, 2022)
"This collection addresses the lack of perspectives beyond Westernized and Anglophone contexts in the digital humanities. Focused on work that has been underappreciated for linguistic, cultural, or geopolitical reasons, contributors showcase alternative histories that detail the rise of the digital humanities in the Global South and other "invisible" contexts and explore the implications of a truly global digital humanities"--